CONCEPTUAL CONTENT OF SUBJECTIVE RIGHT UNDER THE CONDITIONS OF LEGAL INTEGRATION - Калюжний, Ростислав Андрійович; Шапенко, Людмила Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
The purpose of the article is to investigate the essence of subjective right in its relationship with the categories «legal person», «assignment of subjective right» and «exercise of subjective right», as well as to define new substantive characteristics of this concept under the conditions of legal integration. Research methods: the use of the system and structural method and the method of generalization allowed us to analyze the general tendencies of expansion of the content of subjective rights caused by globalization and legal integration transformations of social reality. The dialectical method of scientific cognition as well as the methods of analysis, synthesis and abstraction helped to clarify the content and purpose of the concept under study, identify its main features and structure, as well as the correlation with objective right. Results: scientific research has shown that the issue of the assignment of subjective rights is of great theoretical and practical importance. After all, from a theoretical point of view, understanding the need to correlate human needs with the legal regulation of social relations provides more opportunities for understanding the essence of subjective right, in particular perception of its nature. From the point of view of practice, linking the needs of a person with a specific subjective right will help to consolidate the necessary content of objective right and to establish those competencies of a person necessary to satisfy specific interests. Discussion: the dynamics of the development of social relations and the development of the legal system of Ukraine, which occur under the influence of modern globalization processes, necessitate further scientific understanding of the transformations of the institutional subsystem of the national legal system in the context of detecting changes in the legal status of legal persons.